Performance indicators associated with Indonesia’s consecutive gold-medal success in the 2023 and 2025 SEA games indoor hockey finals - Tri Pujianto; Masrun; Ardo Okilanda; Yendrizal; Roma Irawan (CV. FOUNDAE, 2026)
Background: Performance analysis is increasingly utilized in elite sports to identify key factors contributing to competitive success. However, limited evidence is available regarding the performance indicators underlying Indonesia’s consecutive gold-medal achievements in international indoor hockey competitions. Aims: This study aimed to identify and compare the performance indicators associated with the Indonesian Men’s National Indoor Hockey Team’s success in the 2023 and 2025 SEA Games finals against Malaysia. Method: A quantitative descriptive design employing match performance analysis was adopted. Data were collected from official match statistics and video recordings of the 2023 and 2025 SEA Games finals. The analyzed variables included shots, shots on target, goals scored, successful passes, ball possession, interceptions, attack blocks, goalkeeper saves, fouls, and technical skill effectiveness. Data were examined using descriptive and comparative statistical analyses. Results: Malaysia demonstrated greater dominance in ball possession, passing, and shooting opportunities in both finals. Nevertheless, Indonesia achieved higher scoring efficiency and stronger defensive performance. Shooting effectiveness increased from 57.69% in 2023 to 68.18% in 2025, while defensive indicators, including interceptions, attack blocks, and goalkeeper saves, consistently contributed to match success. Conclusion: Indonesia’s consecutive SEA Games titles were primarily associated with superior finishing efficiency, defensive stability, and effective utilization of scoring opportunities rather than possession dominance. These findings provide evidence-based insights for performance optimization and strategic development in elite indoor hockey.